Dampak Banjir Kota Palembang Terhadap Kecemasan Siswa SMP - Fariza, Jihan; Fitri, Kartika Ayu; Damarsari, Putri Dewita; Romadalia, Riski Nopa; Alrefi, Alrefi (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
The aim of this study is to observe the anxiety levels of students at SMP Negeri 3 Palembang during the 2023/2024 academic year who have been victims of flood disasters. The population in this study includes all students at SMP Negeri 3 Palembang during the 2023/2024 academic year who were affected by the flood disaster, with a sample of 50 students selected using purposive sampling technique. Data collection was carried out using an adapted version of the Screen for Child Anxiety Related Disorders (SCARED) instrument. This type of research is quantitative, employing descriptive statistical methods assisted by Microsoft Excel 2010. The results of the study show that the majority of students at SMP Negeri 3 Palembang during the 2023/2024 academic year who were victims of the flood disaster tend to have moderate levels of anxiety, with a percentage of 74% or 37 respondents. This indicates that the students are beginning to show symptoms of anxiety, although not at a high level.